Sex-Specific Effects of Respiratory Muscle Endurance Training on Cycling Time Trial Performance in Normoxia and Hypoxia - Chambault, Julie; Grand, Grégorine; Kayser, Bengt (Frontiers in Physiology, 2021)
Objectives: We tested the hypotheses that respiratory muscle endurance training (RMET) improves endurance cycling performance differently in women and men, and more so in hypoxia than in normoxia. Design: Prospective pre-post cross-over study with two testing conditions. Method: Healthy active women (7, 24±4 yr, mean±SD) and men (7, 27±5 yr) performed incremental cycling to determine maximum oxygen consumption (VO2peak) and power output (Wpeak), and two 10 km cycling time trials (TT) in normoxia and normobaric hypoxia (FiO2 0.135, 3,500m equivalent), in balanced randomized order. They then did supervised RMET in normoxia (4 wks, 5 days/wk, 30 min/day eucapnic hyperpnea at 60% predicted maximum voluntary ventilation) followed by post-tests. During TTs heart rate, ear oximetry and power output where recorded. Results: VO2peak and Wpeak were unchanged after RMET. TT was improved by 7±6% (P<0.001) in normoxia and 16±6% (P<0.001) in hypoxia. The difference between normoxic and hypoxic TT was smaller after RMET as compared to before (14 vs. 21%, respectively, P<0.001). All effects were greater in women (P<0.001). RMET did not change heart rate or ear oximetry during TTs. Conclusions: We report a greater effect of RMET on cycling TT performance in women than in men, an effect more pronounced in hypoxia. These findings are congruent with the contention of a more pronounced performance limiting role of the respiratory system during endurance exercise in hypoxia compared to normoxia, and more so in women whose respiratory system is undersized compared to that of men.